Lattice Boltzmann Simulation and Visualisation of Adsorption Processes in Complex Geometries - Bernsdorf, Jörg; Jaekel, Uwe; Zeiser, Thomas; Takei, T.; Matsumoto, H.; Nishizawa, K. (Lecture Notes in Computer Science, Computational Science ICCS 2003, 2003)
In this paper, we describe briefly the lattice Boltzmann method, which simulates the flow on a mesoscopic level using a time-, space- and velocity-discrete version of the Boltzmann equation. Further we describe its coupling to the real-time visual simulation library RVSLIB, which allows an efficient client/server based on-line visualisation of the simulation results and/or the image creation on the server. An extension of the standard lattice Boltzmann model for adsorption processes is given together with simulation results and visualisation examples for adsorption in porous media. © Springer-Verlag Berlin Heidelberg 2003.
UnivIS-Import:2015-04-20:Pub.2003.zwiss.rrze.zensys.lattic
Keywords: Adsorption; Lattice Boltzmann; Real time visualisation